Use of circulating fluidized bed combustion bottom ash as a secondary activator in high-volume slag cement. (20th February 2020) - Lee, Hyo Kyoung; Jeon, Sang-Min; Lee, Bang Yeon; Kim, Hyeong-Ki
Highlights: Synergetic effects of CFBC ash and blast furnace slag on the strength and shrinkage was found. The ash could reduce the shrinkage of high-volume slag cement at an early age. Unwanted expansion owing to ash in OPC could be controlled in slag cement. Strength of the HVSC mixture seldom influenced by CFBC ash. Abstract: Circulating fluidized bed combustion (CFBC) bottom ash was used in high-volume slag cement (HVSC) as a secondary activator. To understand the effects of the bottom ash on the HVSC mixture, a series of experiments relating to hydration heat release, hydration products, and the microstructure and engineering properties were performed. For comparison, the ash was also mixed with ordinary Portland cement (OPC). Although the ash could activate the hydration of slag, this did not increase the initial strength of the HVSC mixture. However, the HVSC mixture did not exhibit undesirable swelling caused by ash and the consequent strength reduction that was observed in the OPC mixtures. Furthermore, the ash could reduce the autogenous shrinkage at an early age. When 20 wt% of ash was replaced with slag in the HVSC, the compressive strength of the mixture exhibited a coefficient of variation within 15% depending on the bottom ash content, which is negligible considering the standard deviation.